Impaired colonization of gnotobiotic and conventional rats by streptomycin-resistant strains of Streptococcus mutans. - Bammann, L L (1978)
Colonization of streptomycin-resistant mutants derived from Streptococcus mutans strain LB1, a human isolate, and strain FA-1, a rodent isolate, was studied in gnotobiotic and conventional rats. Mutants resistent to 2.0 mg of streptomycin per ml were isolated by using both stepwise (suffix "R"M) and one-step (suffix "R"1) selections. Rats were infected with mixtures of parental and streptomycin-resistant strains, and the proportions of each strain present in samples from the intestinal canal, tongue dorsum, teeth, and fissure plaque were determined. Combinations of strains investigated were LB1 and FA-1"R"M; FA-1 and LB1"R"M; LB1 and LB1"R"1; FA-1 and FA-1"R"1. In gnotobiotic rats, nonresistant strains predominated in every oral sample studied at 7 and 21 days after infection. Similarly, when conventional exgermfree rats were infected with FA-1 and FA-1"R"1, FA-1 dominated in all samples. Streptomycin-sensitive revertants were not detected in rats monoinfected with strains LB1"R"1 and FA-1"R"1 for 21 days. No antagonistic interactions were observed between the strains in in vitro experiments. Streptomycin-resistent mutants attached to hydroxyapatite treated with rat or human saliva in equal or higher numbers than did parental strains. However, parental strains appeared to grow faster in Trypticase soy broth then streptomycin-resistant mutants. These observations indicate that induction of streptomycin resistance frequently impairs the colonization properties of S. mutans strains, possibly by altering their rate of growth.